Dampak Persepsi Terhadap Inovasi Mendorong Pemikiran Kreatif dalam Organisasi pada CV Sinar Berlian Maumere - da Silva, Yustina Olivia; Lali Laru, Oktavianus Dje; Fabianus, Carol Cornelius; Noni, Maria; Karles, Albertus; Fernando Horong, Gabriel; Natalia, Maria (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Perception in an organization is the process by which individuals in a work environment receive, interpret, and assign meaning to the information, events, or behaviors around them. The approach used is quantitative with a survey method. This approach was chosen to measure the relationship between the perception of innovation and creative thinking in the organization in a systematic and measurable manner. Acceptance of change, openness to new ideas, and influence of the social and cultural environment. Innovation and creativity that are considered relevant, can increase efficiency, and provide new solutions that are easier to accept and adopt.